Assessment of mass characteristics of a wheeled chassis when designing a preventive suspension system - Malinovsky M.P.; Tarichko V.I.; Chikina A.K. (Научно-технический вестник Брянского государственного университета)
Providing first aid outside medical organizations and conducting medical and sanitary measures during the liquidation of consequences of emergency situations is becoming increasingly important and involves the use of ambulances, ambulance buses and resuscitation vehicles, as well as modern mobile complexes based on trucks. These include mobile resuscitation boxes, operating rooms on wheels, vehicles for primary medical examinations, dressing rooms, mobile X-ray rooms, mammography rooms. The specified complex medical equipment requires calibration every time after moving by road transport, which necessitated the creation of a preventive secondary suspension system for the cargo platform based on special wheeled chassis with a large load capacity. Usually, additional vibration protection of transported goods is practically not encountered, including special-purpose ones, to which in-creased requirements for maximum overloads are im-posed. The article presents a suspension system developed by the authors, the peculiarity of which is the preventive nature of the action, consisting in the construction of a predictive algorithm from the driver’s control actions on the controls, unlike most existing stabilization systems with a corrective nature of the action. To achieve a preventive nature of the action by predicting longitudinal and lateral vibrations, brake pedal travel and fuel supply sensors, as well as a steering shaft speed sensor, are used. When developing a suspension system at the stage of preliminary design, it is necessary to know the mass-dimensional characteristics of a special wheeled chassis under different loads. The algorithms of such a system should also take into account the actual location of the center of mass under different loads, which affect many of its operational qualities and parameters. The purpose of this study was to develop a methodology for assessing the residual and full masses of a special wheeled chassis under conditions of infor-mation deficiency.